Methylamine accumulation in cultured cells as a measure of the aqueous storage compartment in the laboratory diagnosis of genetic lysosomal diseases - Kopitz, Jürgen; Harzer, Klaus; Kohlschütter, Alfried; Zöller, Barbara; Blenck, Nahid; Cantz, Michael (American journal of medical genetics, 1996)
Intracellular accumulation of the lysosomotropic compound [14C]methylamine was used to estimate the size of the lysosomal compartment in fibroblasts cultured from patients with a variety of lysosomal storage diseases. In previous work from our laboratory, it was shown that methylamine accumulation was significantly increased in diseases with infantile or juvenile onset and storage of predominantly water-soluble material such as in the mucopolysaccharidoses, mucolipidoses, and oligosaccharidoses. In the present study, methylamine incorporation was abnormally increased in cells from patients with glycogenosis type II and with Niemann-Pick type C disease, whereas it was normal in other sphingolipidoses and in the late-infantile and juvenile forms of neuronal ceroid lipofuscinoses. The methylamine test was also checked regarding its potential use for prenatal diagnostic testing. In model systems with cultured amniotic or chorionic villus cells, lysosomal storage was experimentally induced by the cathepsin inhibitor leupeptin and was readily detected when compared to untreated controls. Cultured amniotic cells from a fetus with mucopolysaccharidosis II were found to incorporate significantly higher amounts of [14C]methylamine than the normal controls. The results indicate that the methylamine accumulation method is an additional tool in the diagnosis and prenatal diagnosis of lysosomal diseases with abnormal storage of water-soluble material. © 1996 Wiley-Liss, Inc.